2014
DOI: 10.1177/0009922814540988
|View full text |Cite
|
Sign up to set email alerts
|

Why Parents Use the Emergency Department During Evening Hours for Nonemergent Pediatric Care

Abstract: Many parents who expect outpatient treatment prefer to take their child to a primary care pediatrician during evening hours, but present to the ED because of lack of primary care access.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 25 publications
2
32
0
Order By: Relevance
“…Patients with self‐pay status or those on Medicaid or the Children's Health Insurance Program also reported significantly more difficulty contacting a clinician on nights and weekends versus those with private insurance . In a study of overnight and weekend pediatric ED visits, 80% of parents reported no night or weekend access to their pediatrician; of those without access, 67.6% of parents would have preferred to see their pediatrician . In the 2007 to 2009 Medical Expenditure Panel Survey of 27,972 adults, individuals whose usual source of care was not available on nights or weekends used the ED more often, and those who had difficulty reaching their primary provider's office after hours similarly were more likely to use the ED for nonurgent conditions …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with self‐pay status or those on Medicaid or the Children's Health Insurance Program also reported significantly more difficulty contacting a clinician on nights and weekends versus those with private insurance . In a study of overnight and weekend pediatric ED visits, 80% of parents reported no night or weekend access to their pediatrician; of those without access, 67.6% of parents would have preferred to see their pediatrician . In the 2007 to 2009 Medical Expenditure Panel Survey of 27,972 adults, individuals whose usual source of care was not available on nights or weekends used the ED more often, and those who had difficulty reaching their primary provider's office after hours similarly were more likely to use the ED for nonurgent conditions …”
Section: Discussionmentioning
confidence: 99%
“…18 In a study of overnight and weekend pediatric ED visits, 80% of parents reported no night or weekend access to their pediatrician; of those without access, 67.6% of parents would have preferred to see their pediatrician. 12 In the 2007 to 2009 Medical Expenditure Panel Survey of 27,972 adults, individuals whose usual source of care was not available on nights or weekends used the ED more often, and those who had difficulty reaching their primary provider's office after hours similarly were more likely to use the ED for nonurgent conditions. 19 Extended hours for primary care access has been associated with reductions in ED utilization in multiple studies in the United States and in other countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests that high‐frequency utilizers of pediatric emergency services also use primary care “sick visits” to address similar complaints . Prior qualitative studies have identified drivers for ED use including perception of illness severity, inability to schedule timely urgent primary care appointments, and the convenience of the ED given other social constraints . However, studies of acute care use are typically conducted with convenience samples of patients who have already made a choice to use the ED, without exploring decision‐making on similar illnesses seen in other settings.…”
mentioning
confidence: 99%
“…Often, pediatric patients visit PEDs during days and hours in which the primary care pediatric centers are closed, particularly on the weekends and in the evenings (12).…”
Section: Discussionmentioning
confidence: 99%